Relationship between cardiovascular dysfunction and hyperglycemia in streptozotocin-induced diabetes in rats - Schaan,B.D. (2004)
Streptozotocin (STZ)-induced diabetes in rats is characterized by cardiovascular dysfunction beginning 5 days after STZ injection, which may reflect functional or structural autonomic nervous system damage. We investigated cardiovascular and autonomic function, in rats weighing 166 ± 4 g, 5-7, 14, 30, 45, and 90 days after STZ injection (N = 24, 33, 27, 14, and 13, respectively). Arterial pressure (AP), mean AP (MAP) variability (standard deviation of the mean of MAP, SDMMAP), heart rate (HR), HR variability (standard deviation of the normal pulse intervals, SDNN), and root mean square of successive difference of pulse intervals (RMSSD) were measured. STZ induced increased glycemia in diabetic rats vs control rats. Diabetes reduced resting HR from 363 ± 12 to 332 ± 5 bpm (P < 0.05) 5 to 7 days after STZ and reduced MAP from 121 ± 2 to 104 ± 5 mmHg (P = 0.007) 14 days after STZ. HR and MAP variability were lower in diabetic vs control rats 30-45 days after STZ injection (RMSSD decreased from 5.6 ± 0.9 to 3.4 ± 0.4 ms, P = 0.04 and SDMMAP from 6.6 ± 0.6 to 4.2 ± 0.6 mmHg, P = 0.005). Glycemia was negatively correlated with resting AP and HR (r = -0.41 and -0.40, P < 0.001) and with SDNN and SDMMAP indices (r = -0.34 and -0.49, P < 0.01). Even though STZ-diabetic rats presented bradycardia and hypotension early in the course of diabetes, their autonomic function was reduced only 30-45 days after STZ injection and these changes were negatively correlated with plasma glucose, suggesting a metabolic origin.